The effectiveness of marketing communications tools by ASNB Melaka: Study case at Institut Perguruan Perempuan Melayu, Melaka / Junainah Jamaluddin - Jamaluddin, Junainah (Faculty of Business and Management, 2008)
Understanding the relative effectiveness of different media for marketing communications has always been challenging. As for Amanah Saham Nasional Berhad, seminars aggressively had been done all over Malaysia; still the impact toward the number of new investors is disappointing. Recently they have organized seminars in Insititut Perguruan Perempuan Melayu (IPPM), Melaka but the results gained also quite disappointed. Thus, in this study we will examine the effectiveness of six marketing communications tools which are personal selling, advertising, sales promotions, sponsorship marketing, publicity and point-of-purchase communications by applying the Hierarchy of Effects Model that were designed by Robert J. Lavidge and Gary A. Steiner in 1961, towards IPPM. Due to low impact on the personal selling for ASB schemes towards IPPM, the researcher identified level of effectiveness of marketing communication tools that had been done factors that will make the messages sent to the audiences more efficiently. For the purpose of this study, descriptive, exploratory and causal research is applied. The researcher also applied self-administered interview to 135 respondents which gone through Stratified Sampling Technique. Moreover, data analysis, cross tabulation, correlation, hypotheses testing and regression gathered through the use of Statistical Package for the Social Science (SPSS). Finally, the finding of the results concludes that personal selling is the most influence factor to the marketing communications effectiveness, which it is correlated to four other factors which are advertising, sales promotions, sponsorship marketing and publicity.